Implementation of the Political Public Relations Approach for DPR Member Dedi Mulyadi through Youtube Channel - Trisno Muldani (IHSA Institute, 2022)
Public Relations (PR) Politics for a member of the National Parliamentary has an essential and strategic role in maintaining good relations with the community. As a member of the DPR RI that the people elected, Dedi Mulyadi is required to publish his daily activities to the public as proof of the transparency of the performance of a people's representative. Along with the times, political public relations must adapt to be more adaptive, collaborative, and flexible. To meet these demands, Political PR must use new media to support its work. In this digital era, one of the new media that can be used in political PR activities is Youtube. This media is optimized by DPR member Dedi Mulyadi to approach Political PR to the community. This study aims to describe the implementation of the Political PR approach to DPR Member Dedi Mulyadi who uses YouTube as a medium. This study uses a qualitative approach with a descriptive method. Data collection was obtained from the results of the documentation. This study indicates that DPR Member Dedi Mulyadi uses a Political PR approach in the form of Political Hype (Political Hype), namely PR work that takes a publicity approach with the formula